Posterior reversible encephalopathy syndrome with spinal cord involvement but without hemisphere lesions: A case report. Issue 2 (January 2019) - Liu, Lu; Dai, Dawei; Cao, Fan; Zhang, Liming; Wang, Xun
Abstract: Rationale: Posterior reversible encephalopathy syndrome (PRES) was termed by Hinchey[1] in 1996. Patients have a reversible vasogenic brain edema in imaging and acute neurological symptoms such as headache, seizures, encephalopathy, and visual disturbances when suffering from hypertension, pre-eclampsia/eclampsia, renal failure, immunosuppressive medications, autoimmune disorders, sepsis, thrombocytopaenia, hypocalcaemia, alcohol withdrawal, and many other potential causes.[2, 3] de Havenon A et al[4] have proposed a new syndrome named PRES with spinal cord involvement (PRES-SCI). The patients with PRES-SCI have similar symptoms these of PRES. Patients have neurologic signs with the spinal cord involved and lesions in magnetic resonance imaging (MRI) extending to the cervicomedullary junction, usually with extreme elevation in blood pressure and a history of hypertensive retinopathy.[4] We administrated a young patient whose condition was consistent with PRES-SCI except for the hemisphere lesions. Patient Concerns: A 20-year-old Asian male patient was admitted for a 1 week history of blurred vision and weakness of the limbs. He has had poorly controlled hypertension for 1 year before admission. In emergency room, his blood pressure could raise to 260/140mmHg. Neurological examinations and cerebral spinal fluid tests were negative. The MRI of the brain and spinal cord showed reversible lesions in the medulla and upper cervical spinal cord that extended to the lower thoracic spine. Diagnosis: Taking into account the characteristic lesions in the MRI as well as the reversible course upon treatment, he was diagnosed PRES-SCI. Interventions: He was treated with medicines for the hypertension. Outcomes: His symptoms rapidly improved and finally the lesions on the MRI of the brain and spianl cord disappeared. Lessons: Clinicians should suspect PRES-SCI when patients have mild or no neurologic signs accompanied with extreme elevation in blood pressure and lesions in spinal cord. Spinal lesions alone may be a subtype of PRES-SCI.